2005
DOI: 10.2320/matertrans.46.2530
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Substrate Temperature and Oxygen Pressure on Crystallographic Orientations of Sputtered Nickel Oxide Films

Abstract: Nickel oxide (NiO) films with NaCl-type structure were deposited onto Corning glass substrates at different substrate temperatures by radio-frequency (RF) magnetron sputtering under an RF power of 200 W. The resulting films were analyzed by grazing-incidence X-ray diffraction, ultrahigh resolution scanning electron microscopy (HR-SEM) and high-resolution transmission electron microscopy (HR-TEM). The relationships among the gas ratio of O 2 , substrate temperature, preferred orientation and microstructure of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…The XRD pattern (Figure 4A ) matches the standard spectrum of JCPDS 4-835 (Figure 4D ) except from two perspectives. Firstly, the peak corresponding to (220) is not obvious, which was consistent with other studies (Chen et al, 2005 ; Jang et al, 2008 ). Jang et al found that there is no (220) peak for NiO after sputter-coating even with heat treatment (Jang et al, 2008 ).…”
Section: Resultssupporting
confidence: 90%
“…The XRD pattern (Figure 4A ) matches the standard spectrum of JCPDS 4-835 (Figure 4D ) except from two perspectives. Firstly, the peak corresponding to (220) is not obvious, which was consistent with other studies (Chen et al, 2005 ; Jang et al, 2008 ). Jang et al found that there is no (220) peak for NiO after sputter-coating even with heat treatment (Jang et al, 2008 ).…”
Section: Resultssupporting
confidence: 90%
“…(111) orientation. Our data agree with prior work which has stated several times that the (111) growth direction tends to be favored when Ni oxide films are produced in the presence of a sufficient amount of oxygen [51][52][53] . are consistent with the morphology of our NiO 1.22 films reported on before [30] .…”
Section: Composition and Structure Of Ni Oxide Thin Filmssupporting
confidence: 92%
“…No specific preferred orientation is observed for the NiO phase in sample #07, but a (111) preferred orientation tends to increase from sample #07 to sample #13 (i.e. for p O2 > 0.13 Pa) as previously observed in similar films [28,29]. In the cubic NiO rock salt structure, the (111) plane corresponds to the pure compact plane of oxygen.…”
Section: Structural Propertiessupporting
confidence: 53%